2009
DOI: 10.5551/jat.no927
|View full text |Cite
|
Sign up to set email alerts
|

Association between Maximal Oxygen Uptake and the Heart Rate Corrected-QT Interval in Postmenopausal Overweight Women

Abstract: Background: Increased aerobic capacity can reduce the incidence of cardiovascular disease and the mortality rate. On the other hand, a prolonged heart rate corrected-QT (QTc) interval is associated with an increased risk of arrhythmias, cardiac sudden death and coronary artery disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Furthermore, the QTc interval is influenced by electrolyte imbalances, such as a reduction in the outward potassium channel currents, or an increase in the inward sodium or calcium channel currents . Our previous cross‐sectional study showed that a prolonged QTc interval correlated with a lower aerobic capacity and an electrolyte imbalance . According to our previous data, a prolonged QTc interval, an electrolyte imbalance and physical activity levels were considered to show a continuous relationship.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the QTc interval is influenced by electrolyte imbalances, such as a reduction in the outward potassium channel currents, or an increase in the inward sodium or calcium channel currents . Our previous cross‐sectional study showed that a prolonged QTc interval correlated with a lower aerobic capacity and an electrolyte imbalance . According to our previous data, a prolonged QTc interval, an electrolyte imbalance and physical activity levels were considered to show a continuous relationship.…”
Section: Discussionmentioning
confidence: 99%
“…26 Our previous cross-sectional study showed that a prolonged QTc interval correlated with a lower aerobic capacity and an electrolyte imbalance. 12 According to our previous data, a prolonged QTc interval, an electrolyte imbalance and physical activity levels were considered to show a continuous relationship.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, an electrocardiogram showing QTc prolongation is an important indicator for treatment and medication in clinical practice [ 4 ]. Many epidemiological risk factors for QTc prolongation have previously been reported, including older age, sex hormones and electrolyte disturbances [ 5 7 ]. Disturbances in serum electrolytes might induce or facilitate clinical arrhythmias by interacting with abnormal myocardial tissue, and this could even occur in a bundle of normal cardiac tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous cross-sectional study (28) noted that a prolonged QTc interval correlated negatively with a lower aerobic capacity, while it positively correlated with the serum sodium level and negatively correlated with the serum potassium concentration in postmenopausal overweight females. Moreover, Franzoni et al (29) reported that patients with anorexia nervosa have a greater QT dispersion than normal body weight females, and oral potassium supplementation (two vials of K-Flebo d , per os) for 4 wk led to a significant reduction in the QT interval dispersion.…”
Section: Discussionmentioning
confidence: 84%